Subjective discomfort during Botulinumtoxin injections dependent on injection site and needle size: a comparison between 30G, 33G and 34G needles - Kämmerer, Till A.; Bertlich, Randolf; Hartmann, Daniela; Jakob, Mark; Weiss, Bernhard G.; Bertlich, Ines; Ihler, Friedrich; Wiggenhauser, Paul Severin; Bertlich, Mattis (Aesthetic plastic surgery, 2024)
Background: Botulinumtoxin application in the face is amongst the most common aesthetic procedures in the head and neck region. It also has numerous medical uses. One of the main reasons for patients to refrain from it is the subjective discomfort that is experienced during injections. Objectives: The study at hand aimed to determine whether needles with 33G and 34G offer an advantage in terms of individual pain perception during botulinumtoxin injections. Methods: We conducted a prospective study where patients were asked to grade subjective discomfort on a visual analogue scale for each region (forehead, glabella, temple) that was treated directly after treatment and 15 minutes after. Patients were treated with 30G, 33G or 34G needles, respectively. Results: Ninety-nine patients that underwent treatment of 189 regions were included in the study. Patients were evenly distributed amongst the different needle sizes and regions. Subjective discomfort was greatest in all regions for 30G needles (3.9  ± 1.6 forehead, 4.3 ± 1.7 glabella and 4.0 ± 1.6 temple) followed by 33G (2.7 ± 1.5 forehead, 2.7 ± 1.9 glabella and 2.2 ± 1.2 temple) and 34G (1.7 ± 1.2 forehead, 1.6 ± 1.4 glabella and 1.6 ± 1.4 temple). All differences between needle size were statistically significant (p < 0.05)Conclusion: 33G and 34G needles seem to offer smaller discomfort during BTX treatments of the head and neck, with 34G being superior to 33G.
Online veröffentlicht: 5. März 2024
Gesehen am 25.07.2024